Thatcher the downing street years - Blakeway, Denys ([S.l.] : Fine Art Productions)
This major award-winning documentary lays bare the clashes of personality, policy and ideology which went on behind the closed door of Number Ten. This video also creates a new form of historical document.
Copy available in DVD format
Editor, Simon Holland ; executive producer, Hugh Scully, Samir Shah
Narrator: Philip Tibenham
Keywords: Thatcher, Margaret; Prime ministers -- United Kingdom -- Biography; Great Britain -- Politics and government